Facile conversion of cysteine and alkyl cysteines to dehydroalanine on protein surfaces: versatile and switchable access to functionalized proteins. - Bernardes, G; Chalker, J; Errey, J; Davis, B (2008)
An efficient and robust oxidative elimination of cysteine to dehydroalanine has been discovered. The reaction is induced by O-mesitylenesulfonylhydroxylamine (MSH) and is compatible with methionine. The key elimination has been executed on protein surfaces and allows ready access to different post-translationally modified proteins through conjugate addition of sulfur nucleophiles to dehydroalanine. Treatment of the resulting thioether with MSH results in regeneration of dehydroalanine, allowing a "functional switch" by subsequent addition of a different thiol.